Bruyantes mécaniques du temps repassé : l’orgue de foire et ses instaurations - Kienholz, Achille (Schweizer Jahrbuch für Musikwissenschaft, 2026)
While the relationship between time and music represents an extensively addressed topic, much less has been said about the concrete efforts undertaken to produce such a relationship by means of specific devices. In this article, I examine how the mechanical organ, a music distributor and a highly developed mediating tool, acts in order to establish the fair as an event and as an institution. My focus lies on the organ’s peculiar ability to store, deliver and repeat – potentially endlessly – musical sequences. I argue that such a feature had a central role in the way showpeople, their work and the time and space occupied by them were defined during the long 19th century. At the intersection of science’s popularization, migration phenomena, concerns about acoustics and strives for professional recognition, barrel and fairground organs, in their very materiality, testify to the active part they took in the shaping of a downplayed, although essential, social area of Western modernity. By giving an account of the time manipulations allowed, through sound, by these instruments, it is therefore possible to get a better grasp on a set of dynamics still relevant to our present aesthetic, historical and political categories.